EFEKTIVITAS AKUN TWITTER @infoPKU SEBAGAI MEDIA INFORMASI ONLINE DI PEKANBARU - Aprina Junika; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Twitter is a social media that is not only effective for communicating, butalso to provide many informations online. An example of a twitter account that isused as an online information media is @infoPKU. This account provides manyinformations concerning Pekanbaru. The theories used in this research arecommunication effectiveness as the main theory and new media as the supportingtheory. The purpose of this research is to investigate how effective this account isas an online information media in Pekanbaru.This research uses a quantitative method which gathered datas usingquestionnaires by google doc that were distributed to hundreds followers of@infoPKU. The datas were also collected using simple random samplingtechnique.This research shows that the effectiveness of @infoPKU as an informationprovider media in Pekanbaru are considered effective. This has been proven bythe result of collected datas that have been measured by six indicator, which areReceiver, Content, Media, Format, Source and Timing. The result was on a scaleof 3,90 effective which means that @infoPKU is effective media as an onlineinformation media in Pekanbaru..Keyword: Communication Effectiveness, @infoPKU Twitter Account, OnlineInformation Media